A comprehensive examination of association between belief in vaccine misinformation and vaccination intention in the COVID-19 context. Issue 7 (3rd July 2022) - Kim, Kwanho; Lee, Chul-joo; Ihm, Jennifer; Kim, Yunjin
ABSTRACT: Misinformation about COVID-19 vaccines is widely available in the public communication environment. Exposure to the misinformation may increase perceived risk of and evoke negative emotions toward COVID-19 vaccines that may eventually reduce COVID-19 vaccination intentions. The negative influences of misinformation may vary by aspects of individuals' social networks. Expanding the reasoned action approach, we proposed a comprehensive model to examine the roles of misinformation beliefs, perceived risk, fear, worry, and social networks in explaining COVID-19 vaccination intentions. We tested the model using survey data of South Korean adults, collected when the Korean government launched its nationwide vaccination program in April 2021 ( n = 744). The results from our step-by-step path analyses indicated that COVID-19 vaccination intentions had positive direct associations with vaccination-specific factors such as attitudes toward, injunctive norms on, and perceived behavioral control over COVID-19 vaccination. Perceived risk was also directly linked to intentions. Among these factors, attitudes and injunctive norms were most strongly related to intentions. Misinformation beliefs and worry had negative indirect relationships with intentions via the mediation of these variables directly connected to intentions. The negative influences of misinformation beliefs were greater among respondents reported stronger tie strengths. Theoretical and practical implications were discussed.